Agricultural extension via radio the Bicol experience - Ombao, Kristina Mae R. (2007.)
"This is a descriptive case study of the Agricultural Training institute's (ATI's) School-on-the-Air (SOA) program in the Bicol Region with the purpose of examining the interplaying factors that affect the implementers' handling and structuring of the program, the nature of SOA message, as well as the factors that influence the listeners' appreciation of this extension method. Three research methods--interviews,content analysis and survey--were used as methods for data gathering. The Model of Communication formulated by Maletzke was used to show the unterplaying variables that influences the SOA implementers, resource persons and announcer in creating and structuring of broadcasts. The Agenda-Setting Theory was also used to explain the influence of communicators' orientations in the way audiences' made sense of the SOA lessons. Maletzke's Communication Model also provided an explanation to the factors that affect the listeners' reception of message. In explaining the dependencies and subjectivities of audience, the Media Dependency Theory was also used. Interview results revealed that the agricultural techologies featured in the broadcasts were priority programs of the Department of Agriculture (DA). The SOA implementers in Region V believed that a greater number of farmers could benefit from this extension method due to its wide reach and credible resource persons who handled the lessons. However, lack of funding and prioritization were some of the most evident constraints encountered in the implementation of the SOA. Survey results showed that the greatest number of respondents in this study were aged 50 years old and above with monthly incomes as low as Php 5,000 and whose major source of livelihood was farming. They listened to the SOA mainly for the desire to learn new farming techniques and in effect, improve their lives. The use of radio in extension, however, had its weak points--such as fluctuating station signal ang power black-outs in the SOA's target areas. In spite of these loopholes, most of the respondents still believed that the radio could be a good source of agricultural innovations featured through the SOA program. The content analysis of the SOA program was measured through the broadcasts' focus, tone and treatment. Data revealed that the SOA program was generally focused on the technology transfer of the Hybrid Rice Production, on of the banner programs of the DA. Findings also showed that the program guests, composed mainly of representatives from farmers' groups, private sponsor companies and government agencies involved in the SOA program were interpretative in their discussions as they elucidated the benefits from hybrid rice farming and the benefits derived from using the products they were promoting. The program resource persons, on the other hand, who handled the core lessons of hybrid rice farming manifested interpretative tone since their discussion of farming concepts and methods were backed-up with practical explanations. With regard to the treatment of broadcasts, the program guests were more proactive in promoting the hybrid rice technology, alongside with the products of program sponsors. The resource person, in contrast, were generally neutral in their treatment of broadcasts."
Vita.
Thesis (M.A. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Radio in agriculture -- Philippines -- Bicol; Agricultural extension work -- Philippines -- Bicol